The Dynamism of Daily Justice: A Person-Environment Fit Perspective on the Situated Value of Justice - Lennard, Anna C.; Matta, Fadel K.; Lin, Szu-Han (Joanna); Koopman, Joel; Johnson, Russell E. (Organization Science, 2022)
Despite the generally positive consequences associated with justice, recent research suggests that supervisors cannot always enact justice, and responses to justice may not be universally positive. Thus, justice is likely to vary in both how much it is received and the employee reactions it engenders. In order to understand the range of justice responses, we develop a dynamic theory of justice by using person-environment fit to take both the value that an individual places in justice and the justice they received into account. Using this framework, we clarify the consequences of congruence versus incongruence in daily justice received and valued, which have implications for treatment discrepancies and subsequent work behavior. We also identify the differences between excess and deficient justice on cognitive and affective responses to justice. Our findings reveal that employees’ experience of justice is more complicated than simply whether the justice they received was high or low on a particular day. Using experience sampling and polynomial regression methods, we observe that not all instances in which employees receive high levels of justice are equivalent. In fact, we find that, depending on justice valued, receiving high levels of justice can be just as detrimental as receiving low levels. Additionally, we find that although both forms of justice misfit (excess and deficiency) cause-negative work outcomes, they affect these outcomes through differential responses to justice — with excess causing increased rumination and deficiency causing decreased positive affect. We conclude by discussing the implications of these findings for extant justice theory and for supervisor-employee work interactions.